Multi-center observational study on occurrence and related clinical factors of neurogenic heterotopic ossification in patients with disorders of consciousness. (16th April 2021) - Estraneo, A; Pascarella, A; Masotta, O; Bartolo, M; Pistoia, F; Perin, C; Marino, S; Lucca, L; Pingue, V; Casanova, E; Romoli, AM; Gentile, S; et al.
ABSTRACT: Aims : to assess occurrence and clinical correlates of neurogenic heterotopic ossifications (NHO) in patients with prolonged disorder of consciousness (DoC). Design : multi-center cross-sectional observational study. Setting : 23 intensive neurorehabilitation units. Subjects : 287 patients with prolonged disorder of consciousness (DoC; 150 in vegetative state, VS, and 128 in minimally conscious state, MCS) of different etiology (vascular = 125, traumatic = 83, anoxic = 56, others = 14). Main Measures : clinical evidence of NHO confirmed by standard radiological and/or sonographic evaluation; Coma Recovery Scale-Revised; Disability Rating Scale (DRS); Early Rehabilitation Barthel Index; presence of ventilator support, spasticity, bone fractures and paroxysmal sympathetic hyperactivity. Results : 31 patients (11.2%) presented NHO. Univariate analyses showed that NHO was associated with VS diagnosis, traumatic etiology, high DRS category and total score, and high occurrence of limb spasticity and bone fractures. A cluster-corrected binary logistic regression model (excluding spasticity available in a subset of patients) showed that only lower DRS total score and presence of bone fractures were independently associated with NHO. Conclusions : NHO are relatively frequent in patients with DoC, and are independently associated with functional disability, bone fractures and spasticity. These findings contribute to identifying patients with DoC prone to develop NHO and requiring special interventions to improve functional recovery.